Assessment of the possible ameliorative effect of curcumin nanoformulation on the submandibular salivary gland of alloxan-induced diabetes in a rat model (Light microscopic and ultrastructural study) - Maha El Shahawy; Mona El Deeb (Saudi Dental Journal)
Background: Nowadays, attention is directed to herbal treatments in an attempt to lessen the adverse effects of diabetes. Nanoformulation of curcumin (NC) was shown to enhance stability and water solubility compared to native curcumin. Objective: To examine the effect of different NC concentrations on the histopathological structure of the submandibular salivary gland of diabetic rats. Methods: 28 rats were divided equally into 4 groups. Group I: Control group, Group II (diabetic), III (diabetic + nanocurcumin low dose), and IV (diabetic + nanocurcumin high dose): Rats of groups II, III and IV were injected with a single dose of alloxan (140 mg/kg) to induce diabetes. After 7 days, groups III and IV were treated for 6 weeks with NC (100 mg/kg/day) for group III, and (200 mg/kg/day) for group IV. Submandibular salivary glands were assessed histologically, immunohistochemically using α smooth muscle actin (α SMA) and ultrastructurally. Results: Diabetic samples showed destruction of parenchymal elements of the gland, with thick fiber bundles encircling the excretory ducts and minimal reaction for α SMA. Amelioration of the gland's architecture was detected in groups III and IV with reduction of collagen deposition and elevation of positive immunoreactivity to α SMA. Conclusion: NC profoundly repaired the induced diabetic histopathological and ultrastructural alterations of the gland in a dose dependent manner.